Superstar or Scholar? African American Male Youths' Perceptions of Opportunity in a Time of Change. (September 2015) - Conchas, Gilberto Q.; Lin, Alex R.; Oseguera, Leticia; Drake, Sean J.
Through a Multiple Marginality Framework, this exploratory case study highlights how African American male youth in an urban high school setting perceive the opportunity structure during the historic election of the first African American President. Youth optimism generated by Obama's election gives students a sense of hope despite the persistent inequality they face in inner-city communities and schools. Findings suggest that the pervasive influence of both structural and cultural factors—such as poverty, racial ideology, racial tracking in schools, and street socialization—help explain students' aspirations and constrained expectations to pursue professional athletics. The implications of this study call for a reemphasis on the relevancy of school and community factors and influences in improving the perceptions of opportunity for African American males.